English as a Foreign Language Teacher Flow: How Do Personality and Emotional Intelligence Factor in? - Sobhanmanesh, Alireza (Frontiers in Psychology, 2022)
Teaching is one of the professions that creates opportunities for individuals to experience flow, a state of complete absorption in an activity. However, very few studies have examined ESL/EFL teachers’ flow states inside or outside the classroom. As such, this study aimed to explore the quality of experience of 75 EFL teachers in flow and also examine the relationships between their emotional intelligence, the Big Five personality traits and the flow state. To this end, the teachers filled out recurrent flow surveys for a week, and also completed emotional intelligence and the Big Five personality questionnaires. It was found that reading was the major flow trigger outside the classroom and teaching and delivering lessons was the most significant flow-inducing activity for the teachers inside the classroom. Furthermore, correlations and independent samples t-tests indicated that all emotional intelligence and personality traits had significant relationships with flow except agreeableness. Finally, multiple regression analysis showed that two personality traits, conscientiousness and openness to experience were the strongest predictors of the flow state. The implications for future flow-related research in the field of applied linguistics are discussed.